Time for global scale‐up, not randomized trials, of uterine balloon tamponade for postpartum hemorrhage. Issue 1 (14th April 2018) - Burke, Thomas F.; Thapa, Kusum; Shivkumar, Poonam; Tarimo, Vincent; Oguttu, Monica; Garg, Lorraine; Pande, Saroja; Fidvi, Juzar; Bangal, Vidyadhar; Ochoa, José; Amatya, Archana; Eckardt, Melody; et al.
Abstract : Global scale‐up of uterine balloon tamponade should be accelerated to end the scourge of unnecessary death and disability from postpartum hemorrhage.